Efektivitas Standar Pelayanan Minimal (SPM) pada Dinas Kependudukan dan Pencatatan Sipil di Merauke provinsi Papua Selatan. - BWARIAT, EMANUEL ULMWAS ARAWAMAN BWARIAT (PAPSEL Research and Consulting, 2025)
This research aims to analyze the effectiveness of Minimum Service Standards (MSS) implementation at the Department of Population and Civil Registration (Disdukcapil) in Merauke Regency, South Papua Province. MSS are crucial instruments for guaranteeing community rights to quality basic services, including civil administration services. Despite their establishment, challenges persist in ensuring that services provided align with the stipulated standards. The research employed a descriptive qualitative approach, collecting data through in-depth interviews, observation, and document analysis. Key informants included the head of the department, service-providing staff, and representatives of community service users. The findings indicate that MSS implementation at Merauke Disdukcapil has generally been underway, though its effectiveness varies across service types. Some MSS indicators, such as service waiting times and cost certainty, have been well-met. However, challenges are still present in aspects like the availability of adequate human resources, sub-optimal socialization of MSS to the community, and the need for improved supporting infrastructure. Limited access to information and public understanding of service rights also act as inhibiting factors. Thus, the effectiveness of MSS at Merauke Disdukcapil can be enhanced through strengthening human resource capacity, improving facilities and infrastructure, and intensifying socialization efforts. This study recommends the necessity of regular evaluation and continuous improvement to ensure excellent civil administration services for all communities in Merauke.